Peran Sistem Informasi Akuntansi dalam Meningkatkan Transparansi Keuangan Perguruan Tinggi: Studi Kasus Implementasi E-Government di Politeknik Negeri Medan: The Role of Accounting Information Systems in Increasing Higher Education Financial Transparency: Case Study of E-Government Implementation at Medan State Polytechnic - Sekedang, Yusnar Yusuf; Napitupulu , Ilham Hidayah (KIRANA : Social Science Journal, 2025)
This article reviews the role of accounting information systems in increasing financial transparency with the implementation of e-government. The purpose of writing this article is to build a hypothesis of the influence between two variables that will be used in further research. The results of this literature review article can be tested scientifically to see the truth empirically.